Muslim Law Courts and the French Colonial State in Algeria - Christelow, Allan (Princeton : Princeton University Press, 2014)
Allan Christelow examines the Muslim courts of Algeria from 1854, when the French first intervened in Islamic legal matters, through the gradual subordination of the courts and judges that went on until World War I. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of.
Cover; Biographical Notes; Archival Sources
Description based upon print version of record.
Keywords: Algeria -- History -- 1830-1962.; Islamic courts -- Algeria; Islamic courts -- Algeria; Algeria -- History -- 1830-1962.; RELIGION / Islam / General; Electronic books